IMPROVING DIGITAL ACCOUNTING QUALITY BY USING ACCOUNTING DIGITAL APPLICATION IN GAMPONG SUKAJADI KEBUN IRENG LANGSA LAMA DISTRICT LANGSA CITY - Rahmi Meutia; Maulana Rahman; Iqlima Azhar; Asnidar (LPPM dan PM Universitas Samudra, 2021)
Langsa City has 3,579 Micro, Small & Medium Enterprises (MSMEs) which are divided into 5 sub-districts in Langsa City. Of course our daily sights and activities cannot be separated from various services and goods created by MSME actors. GampongSukajadiKebunIreng is one of the areas where various MSMEsbusinesses take place. Business actors say that there is still a lack of a touch of technology in running their business, especially in sales transactions record that manually done, even they do not record sales transactions because they do not know how, and do not understand the importance of recording transactions.Some business actors think it is enough to calculate by themselves and just remember how much money issued for capital, sales created, and profit earned. Based on these problems, the service team wants to help introduce digital bookkeeping.The implementation method is in the form of counseling and socialization the importance of accounting, conduct digital accountingtraining and direct assistance. By having thesesactivities we hope participants will understand the importance of accounting and be able to do digital accounting. The goals are they can know sales cash flow, havemonthly transactions record, know sales record and several other benefits obtained for increasing their business, help family’s economic and in general will support of GampongSukajadiKebunIreng’s economic.